Augmented reality media Assemblr Edu in Biology learning of the excretory system to increase student learning interest - Annisa Rezki Samosir; Kartika Manalu (Himpunan Pengembang Kurikulum Indonesia, 2025)
This study aims to develop and implement Augmented Reality (AR)-based learning media using the Assemblr Edu application in the context of Biology learning, especially on the excretory system material. The method used is Research and Development (RnD) with a 4D development model, which consists of four stages: Define, Design, Develop, and Disseminate. In the Define stage, needs analysis is conducted through interviews with teachers and questionnaires to students to identify challenges in learning. The Design stage includes making storyboards and developing interactive 3D organ excretory models. In the Develop stage, AR media is validated by material and media experts, and tested in class XI F1F, consisting of 36 students. The validation results show that the AR Assemblr Edu media achieved a score of 95.29 precent, which is considered